1992
DOI: 10.2334/josnusd1959.34.28
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Antiseptics on Bacteremia Following Tooth Extraction.

Abstract: The effect of local irrigation of the gingival sulcus, which is considered an important source of bacteremia following dental procedures, with three different antiseptic solutions including hydrogen peroxide, chlorhexidine and povidone iodine, on the frequency of bacteremia after tooth extraction was determined, and the efficacies of the three antiseptics were compared. Although all the antiseptic solutions reduced the frequency of bacteremia to various degrees, povidone iodine was the most effective, and seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
2
8
0
1
Order By: Relevance
“…The authors conclude that this antiseptic is very effective in reducing oral cavity bacterial counts up to 1 hour from the start of operation, which makes it suitable for shorter procedures (oral surgery in local anaesthesia). These results are supported by several smaller studies 1,7,21,23,36 . The authors also noticed that its favourable organo-leptic qualities are important when the oral cavity is preoperatively washed in awake patient.…”
Section: Discussionsupporting
confidence: 88%
“…The authors conclude that this antiseptic is very effective in reducing oral cavity bacterial counts up to 1 hour from the start of operation, which makes it suitable for shorter procedures (oral surgery in local anaesthesia). These results are supported by several smaller studies 1,7,21,23,36 . The authors also noticed that its favourable organo-leptic qualities are important when the oral cavity is preoperatively washed in awake patient.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, broad-spectrum degerming rinses, such as povidone-iodine, chloramine-T, and chlorhexidine, have been shown to reduce the incidence of bacteremia when administered as a rinse or irrigation prior to the extraction procedure or instrumentation, and povidoneiodine was shown to be the most potent in reducing the incidence (84,121,127,144).…”
Section: Tooth Extractionmentioning
confidence: 99%
“…Povidone‐iodine mouthrinse/gargle has shown a reduction in gingival surface bacteria by about 33% compared to 8% by the control solution (47). Also, subgingival irrigation with povidone‐iodine prior to tooth extraction has reduced the incidence of bacteremia by 30–50%(36, 38, 48–53), although not in all studies (54). The American Heart Association has suggested that antiseptic mouthrinses such as povidone‐iodine applied immediately prior to dental procedures might reduce the incidence or magnitude of bacteremia (55).…”
Section: Povidone‐iodinementioning
confidence: 99%